2004
DOI: 10.1029/2003jb002498
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in P wave attenuation in the Loma Prieta rupture zone

Abstract: [1] Clusters of recurring, nearly identical microearthquakes have been recorded near Loma Prieta, California. Such events make possible direct measurement of temporal changes in the attenuation operator t* along fixed paths under what are tantamount to laboratory conditions. Analysis of almost 10 years of P wave data following the 18 October 1989 Loma Prieta, California, main shock (M = 7.0) reveals a large-amplitude t* increase within the first 3 weeks of the main shock. A gradual t* recovery toward its level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Other studies have reported postseismic changes in t ∗ of similar magnitude (e.g., Chun et al . []). This signal could originate from time‐dependent variations in the source or along the travel path.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Other studies have reported postseismic changes in t ∗ of similar magnitude (e.g., Chun et al . []). This signal could originate from time‐dependent variations in the source or along the travel path.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…They have identical source parameters and produce nearly identical seismograms at the same stations. Repeating events are therefore often used to identify temporal changes in the medium [see, e.g., Beroza et al , 1995; Baisch and Bokelmann , 2001; Chun et al , 2004]. In the Parkfield region these repeating sequences of earthquakes have been found to be quite common [ Nadeau et al , 1995; Nadeau and Johnson , 1998].…”
Section: Stress Drop Resultsmentioning
confidence: 99%
“…Furthermore, we are not taking into account any short‐term temporal changes to the stress drop change imposed by the main shock due to, e.g., healing processes. Fault zone healing has been observed with other seismic methods at several locations in California [e.g., Li et al , 1998, 2003; Chun et al , 2004; Li et al , 2006]. Such changes are difficult to assess with our method since we require a large number of events per grid bin in order to determine spatial variations of source parameters reliably.…”
Section: Discussionmentioning
confidence: 95%
“…For such reasons, seismic data and velocity field analysis are used on a daily basis in the oil industry to quantify the oil content and the identify fluid properties, i.e., oil or gas. In seismotectonics, a key unanswered question is whether earthquakes and volcanic eruptions can be predicted by quantifying time dependent precursory damage accumulation using elastic wave velocity variations (CHUN et al, 2004;VOLTI and CRAMPIN, 2003;GAO and CRAMPIN, 2004). Thus the understanding and quantification of elastic wave velocity variations is critical to extract information on the physical state of rocks from seismic and seismological data.…”
Section: Introductionmentioning
confidence: 99%